2010
DOI: 10.1007/s11661-010-0351-y
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Characterization of Cu-Al-Ni Shape Memory Alloy Strips Prepared from Elemental Powders via a Novel Powder Metallurgy Route

Abstract: In the present work, Cu-Al-Ni shape memory alloy strips were prepared successfully from premixed elemental Cu, Al, and Ni powders in the ratio 82:14:4 (wt pct) by a novel processing route consisting of preparing powder preforms, sintering, and unsheathed hot rolling of the sintered preforms. Subsequently, the hot rolled strips were homogenized. The as-rolled strips consisted of two phases-a and b¢. A postconsolidation homogenization of the hot rolled strips was carried out at 1173 K (900°C) for different time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The reason behind the fact that a transformation was observed in the epitaxially grown (200) textured austenite thin film whereas no change was seen in the randomly oriented polycrystalline one could be related to size effects. Size effects, such as the volume of the material or structural components including precipitate particles and grains in polycrystals, have a huge influence on the martensitic phase transformation [37]. Decreasing grain size and decreasing twin separation cause an increase in strain energy and twin interfacial energy which, in turn, increases the energy barrier [38].…”
Section: Resultsmentioning
confidence: 99%
“…The reason behind the fact that a transformation was observed in the epitaxially grown (200) textured austenite thin film whereas no change was seen in the randomly oriented polycrystalline one could be related to size effects. Size effects, such as the volume of the material or structural components including precipitate particles and grains in polycrystals, have a huge influence on the martensitic phase transformation [37]. Decreasing grain size and decreasing twin separation cause an increase in strain energy and twin interfacial energy which, in turn, increases the energy barrier [38].…”
Section: Resultsmentioning
confidence: 99%
“…This diffractogram shows many peaks suggesting a multi-phase alloy. In this diffractogram, there are the peaks of the Al, the peaks of CuNi [14,44], the peaks of NiAl [45,46] and those of the austenite phase of the Cu-based SMAs [47,48].…”
Section: Characterization Of the Superelasticitymentioning
confidence: 99%
“…This makes the process more time consuming and economically unviable. 22 Recently, Vajpai et al 23 have prepared SMA strips by the milling of the elemental powder mixture for a shorter duration (8 h) followed by secondary processing. However, it was observed that the homogenisation treatments required much longer time to produce chemically homogeneous strips.…”
Section: Introductionmentioning
confidence: 99%